Microstructural evolution and mechanical behaviour of alkali activated fly ash binder treated clay. (24th May 2021) - Coudert, Elodie; Deneele, Dimitri; Russo, Giacomo; Vitale, Enza; Tarantino, Alessandro
Highlights: Alkali activated fly ash binder enhances engineering performances of clayey soils. Microstructural evolution of alkali activated fly ash has been investigated. Microstructural changes occur around reactive calcium-containing phases Progressive filling of capillary pores by new compounds has been detected. Abstract: This work focuses on the use of alkali activated fly ash-based binder to enhance engineering characteristics of soft clay-rich soils and as a substitute to standard stabilisers (e.g., lime or cement). Especially, it examines the microstructural evolution of a calcium-rich fly ash from coal combustion-based binder activated by a sodium-based alkaline solution. To this end, the processes generating the microstructure and the evolution of the pore network over time are investigated. A second point addressed by this study is how the presence of kaolin particles affects the microstructural features of the binder. The microstructure has therefore been investigated by considering the binder alone and the binder mixed with kaolin. The effects of microstructural evolution have been observed at macroscopic level by means of one-dimensional compression tests. The combination of completing techniques has been used including Optical microscopy, Scanning Electron Microscopy and Mercury Intrusion Porosimetry in order to gain an overview of the complex pore structure. Microstructural changes occur around calcium-containing phases derived from fly ash which are the reactive phases of the system. Namely, the dissolution of calcium-rich grains leads to the formation of new compounds that first cover the grain surfaces and then further grow into the available space. Furthermore, the evolution of the pore network over time is characterized by a progressive filling of capillary pores by new compounds while small nanometric pores are being formed and associated with the newly formed silicate-calcium chains. Similar tendencies are observed when the binder is mixed with the soil although the general porosity is lesser due to the filling of pores by small-sized kaolinite platelets. Experimental evidences at microscale level have been linked to the macroscopic behaviour of treated soil.